A multi-level approach to modeling language extension in the Enterprise Systems Domain. (December 2015) - Atkinson, Colin; Gerbig, Ralph; Fritzsche, Mathias
Abstract: As the number and diversity of technologies involved in building enterprise systems continues to grow so does the importance of modeling tools that are able to present customized views of enterprise systems to different stakeholders according to their needs and skills. Moreover, since the range of required view types is continuously evolving, it must be possible to extend and enhance the languages and services offered by such tools on an ongoing basis. However, this can be difficult with today׳s modeling tools because the meta-models that define the languages, views and services they support are usually hardwired and thus not amenable to extensions. In practice, therefore, various workarounds have to be used to extend a tool׳s underlying meta-model. Some of these are built into the implemented modeling standards (e.g. UML 2, BPMN 2.0 and ArchiMate 2.0) while others have to be applied by complementary, external tools (e.g. annotation models). These techniques not only increase accidental complexity, they also reduce the ability of the modeling tool to ensure adherence to enterprise rules and constraints. In this paper we discuss the strengths and weaknesses of the various approaches for language extension and propose a modeling framework best able to support the main extension scenarios currently found in practice today.